Comparative thermal tolerance of haploid and diploid phases of two intertidal Antarctic red algae Iridaea cordata and Sarcopeltis antarctica - Navarro Martinez, Nelso Patricio; Saez, Claudio A.; Rodriguez-Rojas, Fernanda; Gomez, Ivan; Huovinen, Pirjo; Jofre, Jocelyn; Celis-Pla, Paula S. M. (My University, 2025)
Physiological and biochemical responses to elevated temperatures were studied in the isomorphic tetrasporophyte (diploid) and gametophyte (haploid) phases of two Antarctic red macroalgal species (Sarcopeltis antarctica, former Gigartina skottsbergii-and Iridaea cordata), assessing whether ploidy affects the responses to extreme and fast warming events. The tetrasporophyte and gametophyte fronds of both species were exposed in the laboratory to 2 degrees C (control) and 8 degrees C (warming event) for up to 3 days. Photosynthetic performance and concentrations of chlorophyll a, total carotenoids, and mycosporine-like amino acids (MAAs) were determined. Inter-and intraspecific differences in physiological and biochemical responses to temperature were observed. Temperature increases slightly stimulated photosynthetic activity (Fv/Fm) over 15 % at 8 degrees C only in gametophytes of both species. Intraspecific variation in the content of MAAs and total carotenoids was also observed, with tetrasporophytes of S. antarctica and gametophytes of I. cordata evidencing a significative 60 % MAA content decrease (accompanied by a slight increase in total carotenoid) at 8 degrees C. These results highlight the role of carotenoids in the acclimation to elevated temperature and MAA content at the lowest ones. Although some intraspecific differences in the responses of haplo-diplontic life cycle phase were observed, there were low effects of exposure to 8 degrees C on photochemistry, outlining the physiological tolerance of both ploidy phases of intertidal species to extreme pulses of temperature increases in Antarctica.
Keywords: red algae; sarcopeltis; iridaea; mycosporine-like amino acids; ploidy